2022
DOI: 10.1021/acsami.2c10216
|View full text |Cite
|
Sign up to set email alerts
|

Self-Enhancing Photoelectrochemical Properties in van der Waals Ferroelectric CuInP2S6 by Photoassisted Acid Hydrolysis

Abstract: Transition metal thiophosphate, CuInP2S6 (CIPS), has recently emerged as a potentially promising material for photoelectrochemical (PEC) water splitting due to its intrinsic ferroelectric polarization for spontaneous photocarrier separation. However, the poor kinetics of the hydrogen evolution reaction (HER) greatly limits its practical applications. Herein, we report self-enhancing photocatalytic behavior of a CIPS photocathode due to chemically driven oxygen incorporation by photoassisted acid oxidation. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 46 publications
(67 reference statements)
0
7
0
Order By: Relevance
“…The Raman spectrum of exfoliated CIPS flakes on SiO 2 substrate shows 314.5 cm −1 for the cation, 102.2 cm −1 for the anion, 267.1 cm −1 for d(S–P–S) modes, and 374.7 and 449.4 cm −1 for ν(P–P) and ν(P–S) modes. [ 2c,4,13c,31 ] The exfoliated CIPS single crystal sample quality is characterized by SEM‐EDS (Scanning electron microscopy (SEM) and energy‐dispersive X‐ray spectroscopy (EDS)) mapping as shown in Figure S1 (Supporting Information), which shows that each element is uniform and located on the flake.…”
Section: Resultsmentioning
confidence: 99%
“…The Raman spectrum of exfoliated CIPS flakes on SiO 2 substrate shows 314.5 cm −1 for the cation, 102.2 cm −1 for the anion, 267.1 cm −1 for d(S–P–S) modes, and 374.7 and 449.4 cm −1 for ν(P–P) and ν(P–S) modes. [ 2c,4,13c,31 ] The exfoliated CIPS single crystal sample quality is characterized by SEM‐EDS (Scanning electron microscopy (SEM) and energy‐dispersive X‐ray spectroscopy (EDS)) mapping as shown in Figure S1 (Supporting Information), which shows that each element is uniform and located on the flake.…”
Section: Resultsmentioning
confidence: 99%
“…showed piezoelectricity assisted hydrogen generation by photocatalysis using PbTiO 3 /CdS heterostructures wherein, approximately nine times higher H 2 generation is achieved rather than traditional photocatalysis. Wang et al [36] . showed improved PEC performance using ferroelectric CuInP 2 S 6 and oxygen doping technique which lowers the fermi level, and thus improves the HER kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Huang et al [35] showed piezoelectricity assisted hydrogen generation by photocatalysis using PbTiO 3 /CdS heterostructures wherein, approximately nine times higher H 2 generation is achieved rather than traditional photocatalysis. Wang et al [36] showed improved PEC performance using ferroelectric CuInP 2 S 6 and oxygen doping technique which lowers the fermi level, and thus improves the HER kinetics. Similarly, Kushwaha et al [37] reported the electrocatalyst (Bi 0.5 Na 0.5 TiO 3 ) in which improved OER kinetics and mass activity are reported which is attributed to ferroelectricity.…”
Section: Introductionmentioning
confidence: 99%
“…41 Further research has revealed the excellent H 2 production activity of transition metal thiophosphates. 42 Xia et al fabricated the S-scheme TiO 2 /FePS 3 heterojunction through the self-assembly of TiO 2 nanoparticles and FePS 3 nanosheets. The H 2 evolution rate on TiO 2 /FePS 3 was increased 16.86 times after the introduction of FePS 3 , much faster than that of TiO 2 alone.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The maximum H 2 production rate was 36 times higher than that of pure TiO 2 nanosheets . Further research has revealed the excellent H 2 production activity of transition metal thiophosphates . Xia et al fabricated the S-scheme TiO 2 /FePS 3 heterojunction through the self-assembly of TiO 2 nanoparticles and FePS 3 nanosheets.…”
Section: Introductionmentioning
confidence: 99%